Synthetic preparation of novel 3D Si/TiO2–Ti2O3 composite nanorod arrays as anodes in lithium ion batteries1. Issue 47 (27th May 2015) - Zhong, Yuan; Yue, Chuang; Chen, Binbin; Sun, Shibo; Zheng, Mingsen; Zhao, Libo; Wu, Suntao; Li, Jing; Kang, Junyong; Lin, Liwei
<x xml:space="preserve">Abstract</x> A novel 3D Si/TiO2–Ti2O3 nanorod array composite prepared by a solvothermal method used as anode in Li-ion batteries.